(3GdUfGYI GdeGdjI GdMOjKI h GJLGgGJ GdJLGQI GdOhdjIs - (3SejQ eMeO(B, (3YHO GdYRjRs ((3GdGScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2011)
(3GdfbhO h GdHfhc h GdUfGYI GdeGdjI GdMOjKI, GdfbhO cebOeI ddCYeGd GdeUQajI, GdHfhc h gjcd GdLgGR GdeUQaj, GdUfGYI GdeGdjI GdMOjKI h JfhjY GdNOeGJ GdeGdjI h GdeUQajI, YGdejI GdNOeGJ GdeUQajI h GdbhGYO GddQbGHjI GdOhdjI ddLfI HGRd, JMdjd h Jbjje GdCOGA GdeGdj ddHfhc, GdJLGQI GdOhdjI h GJLGgGJgG, GdacQ GdcdGSjcj h GdfjhcdGSjc, GdGbJUGOjhf GdeMOKhf ef GdLGJ Gdi efXeI GdJLGQI GdYGdejI, HQhJhchd GdefGWb GdUfGYjI GdeDgdI `` GdchjRs
Keywords: (3GdGOGQIs; (3GdGbJUGOs; (3GdHfhcs; (3GdJLGQIs; (3GdfbhOs